Two Cordillera Legends from Fil-Hispanic Literature: “El Arbol de Oro” and “Antamok” - Imson, Ma. Elinora Peralta (Linguae et Litterae; 2008, 2010)
Leafing through the pages of Manuel Ramirez Guerrero’s Prosa Literaria (Manila 1921) we come across “El árbol de oro” (The Gold Tree)* and “Antamok”, two tales about the Cordillera. The first, it is specified, is a “leyenda igorrota” (an Igorot legend) that explains “el origen de las minas” (Guerrero, 64), that is, the origin of the gold mines in the area. Although no explicit statement is made to identify the second tale as a legend, we soon discover that it too explains how something came to be, this time “el origen del nombre de la mina” (Guerrero, 119) or how the mine “Antamok” got its name. Philippine folklorist Fr. Francisco Demetrio confirms that both stories are indeed legends, but does not elaborate on the matter any further (Demetrio 1969).